Dietary Supplementation of Rauvolfia Vomitoria Root extract as a Phytogenic Feed additive in Growing Rabbit diets: Haematology and Serum Biochemical Indices - Adewale, A.O; Alagbe, J.O; Adeoye, Adekemi Grace (Research Parks Publishing LLC, 2021)
The objective of the present study was to determine effect of dietary supplementation of Rauvolfia vomitoria root extract (RVME) as a phytogenic feed additive in growing rabbit diets: haematology and serum biochemical indices. Thirty (30) weaned rabbits of mixed breed and sex between 6-7 weeks with an average weight of 530.9 and 533.0 grams were divided into five treatments with three replicates per treatment consisting of 2 rabbits per replicate in a completely randomized design. Rabbits in treatment 1 (T1) were fed basal diet with 0 % RVME while T2, T3, T4 and T5 were given RVME at 20 ml, 40ml, 60 ml, and 80 ml/litre of water respectively. The experiment lasted for 12 weeks; food and water were provided ad libitum and all other management were strictly observed. Data collected were used to evaluate the some haematological and serum biochemical indices of animals. Haematological parameters covered pack cell volume (PCV), haemoglobin (Hb), red blood cell (RBC), mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC), white blood cell (WBC) and its differentials while serum analysis contained total protein (Tp), globulin, albumin, creatinine, urea, calcium, phosphorus, sodium, chloride, aspartate serum aminotransferase (AST), alanine amino transferase (ALT) and alanine phosphatase (ALP). All the haematological parameters were significantly (P ˂0.05) different among the treatment. Creatinine, urea and chloride ions not influenced by the dietary treatments (P > 0.05) while the other serum biochemical parameters were significantly (P ˂0.05) affected by RVME. Increasing the level of RVME from 20 ml to 80 ml tended to reduce ALP, AST and ALT values. It was concluded that feeding rabbits RVME at 80 ml/ liter did not cause any negative effect on the health of the animals; the data revealed that all values were within the physiological reference range for rabbits